Supply chain logistics management. - Bowersox, Donald J.; Closs, David J.; Cooper, M. Bixby; Bowersox, John C. (McGraw-Hill series in operations and decision sciences., 2024)
This textbook examines traditional logistics issues within the context of the supply chain. It provides a solid foundation that clearly describes the role of logistics within the supply chain.